The Process of Strategic Urban Planning: a Case of Iran - Akhbari, Mohammad (International Journal of Bio-resource and Stress Management, 2023)
This paper tries to analyze the concept of strategic planning and then explains the concept of strategic planning and analysis processes acceptable range for this type of planning to introduce a list of important issues. The origin of strategic planning is described in the beginning to explain the causes of this approach to planning in recent decades and then the concepts associated with the word strategic are rectified. The strategy is then scheduled to scrutinize the issue focusing on the strategic planning process.